Використання трикутних норм для побудови алгебр з операціями логарифмічного типу - Воробель, Р.А. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Method for algebras construction, which are base strict additive generators of triangular t-norms is presented. Logarithmic type functions are used for such generators. Construction of algebras for set [0, M] and set (0, ∞)) are shown. Examples for new logarithmic type algebras are presented.